Design of the state predictive model following control system with time-delay - Wang, Dazhong; Wu, Shujing; Okubo, Shigenori (Zielona Góra: Uniwersytet Zielonogórski)
Time-delay systems exist in many engineering fields such as transportation systems, communication systems, process engineering and, more recently, networked control systems. It usually results in unsatisfactory performance and is frequently a source of instability, so the control of time-delay systems is practically important.
Keywords: state predictive control; time-delay; model following control system (MFCS); TCP/AQM network; congestion control